Josep Puig i Cadafalch and the construction of a Catalan national imagination (1880-1950) - Mallart, Lucila (2016)
This thesis explores the making of a cultural and political imagination of Catalonia in the late nineteenth and early twentieth centuries, in order to re-think the nature of nationalism in modern Europe. Although in some respects the Catalan story follows some well-known patterns of national identity construction, it is distinctive in others. Its spatial dynamics were rather particular, because they traverse traditional divides between regionalism and nationalism. The three main sections of the thesis are devoted to three spatial tiers of identity construction – the city, the state, and Europe – and draw on the projects of Josep Puig i Cadafalch (1867-1956), famous Catalan politician, man of letters, architect, art historian, and president of the proto-autonomous Catalan government between 1917 and 1923. Puig’s personal archive, made available to researchers for the first time in 2006, allows me to cast fresh light on the interplay between culture and politics in this seminal historical moment.